Quantitative assessment of the genetic types and sources of natural gas in well Y5 of the north slope of Baiyun sag - Wang, Xudong; Qiu, Nansheng; Zhang, Xiangtao; Peng, Guangrong; Chen, Cong; Zhang, Yinglin (Frontiers in Earth Science, 2025)
The exploration of natural gas in the Baiyun Sag of the Pearl River Mouth Basin (PRMB), South China Sea have attracted extensive attentions in recent years. However, considerable controversy remains regarding the origin and main source rocks for the discovered natural gas in this area. In this study, we established a quantitative method for distinguishing the origin and source rock of natural gas by combining geochemical indicators and chemical kinetics. The results show that the natural gas in the Well Y5 block on the northern slope of Baiyun Sag was of thermogenic origin and are mainly derived from Paleogene source rocks with minor contribution of natural gas generated by oil cracking below layer ZH440. The crude oil cracking gas accounts for approximately 6%. The mixture of kerogen degradation gas with a small amount of crude oil cracking gas caused an inversion in the carbon isotope sequence of ethane and propane. The natural gas in the well Y5 area was mainly generated from delta and shallow lake source rocks after 11 Ma. The findings suggest that natural gas was accumulated in shallow, high-quality reservoirs in the early stage and deep, tight reservoirs in the late stage.